Diversity of endophytic bacteria of mulberry (Morus L.) under cold conditions - Chen, Chuan-jie; Guo, Guang; Li, Meng; Liang, Xiao-yan; Gu, Yin-yu (Frontiers in Microbiology, 2022)
Endophytic bacteria are known to impact the growth and fitness of agriculturally relevant plants. However, there are limited reports describing endophytic bacteria related to mulberry (Morus L.). The present study used Illumina-based 16S rRNA gene sequencing to investigate the endophytic bacterial communities of two mulberry cultivars with differing resistance to low temperature, under cold conditions. In most cases, the bacterial communities of endophytes in the root exhibited higher richness compared with those in the stem, and the communities in resistant cultivar X792 exhibited higher richness compared with those of the sensitive cultivar “Da Shi” (DS). The difference in the proportion of unique operational taxonomic units showed the same trend. The number of genera with significant differences in abundance was greater between organs than between months, and greater between months than between cultivars. Microbial diversity analysis showed that Proteobacteria and Actinobacteria were the dominant phyla in all samples, while Pseudomonas, Steroidobacter, and Rhodococcus were the dominant genera in different samples. There were significant differences between cultivars DS and X792 in the relative abundance of Pseudomonas, Acidibacter, Frigoribacterium, Gaiella, and Pseudokineococcus. PICRUSt predictions indicated that the relative abundances of endophytic bacteria in membrane transport and signal transduction were significantly higher in the stem of resistant cultivar X792 in January compared with that of sensitive cultivar DS. Analysis of β-Diversity also revealed distinct differences in endophytic bacterial communities of stem and root, and communities of the stem in January and February. The complex correlation of the endophytic communities was higher in sensitive mulberry cultivar DS compared with resistant cultivar X792, in the stem compared with the root, and in January compared with February. Overall, findings from this study suggested that the diversity and community structure of endophytic bacteria in mulberry were significantly influenced by organs and months, followed by the host cultivar. The study provides insight into the complex microbial diversity of mulberry under cold conditions.